Pengaruh Model STAD Terhadap Hasil Belajar Siswa Dalam PKn Di Kelas IV SDN 03 Simpang Haru - Marta, Dara; Reinita, Reinita; Hamimah, Hamimah (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
This research aims at finding out the effects of using the STAD Model toward students learning outcomes of the Civics subjuct at class IV. This quasi experiment applied the non-equivalent control group design. The population was all 4th grade students of SDN 03 Simpang Haru. The samples were the students of class IVA and IVB. It was found that the average score of the control group students’ posttest was 82.83 and the experiment group’s score was 87.50. The score of tcount was -3.021 with the P-Value of 0.004. Thus, the score of the P-Value was lower than α = 0.05. It means H0 is denied